2018
DOI: 10.1101/392928
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Intact mast cell content during mild head injury is required for the development of latent pain sensitization - implications for mechanisms underlying post-traumatic headache

Abstract: Highlights• Administration of an anti-CGRP mAb does not block ongoing meningeal mast cells (MCs) degranulation following a mild closed head injury (mCHI).• mCHI-evoked cephalic mechanical hyperalgesia does not involve acute degranulation of MCs.• Depletion of meningeal MCs content prior to mCHI blocks the development of chronic latent sensitization to the headache trigger glyceryl trintrate (GTN) following recovery from the initial mCHI-evoked acute cranial hyperalgesia• GTN-evoked delayed cephalic and extrace… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 54 publications
2
15
0
Order By: Relevance
“…Here, to produce a more severe CHI we increased the gravity force by employing a heavier mass (450 g weight), and maintained the same height as in our previous CHI paradigm. The finding that the 450 g CHI paradigm was associated with a ~20% mortality rate, while our earlier studies indicated no mortality using the milder 250 g CHI paradigm (9,22) points to increased injury severity, and is in agreement with previous studies that investigated the effects of a graded mechanical impact levels (27). Our open-field testing data indicated no change in total distance traveled suggesting no impairment in gross motor activity, similar to the effect of a 250 g weight drop injury.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Here, to produce a more severe CHI we increased the gravity force by employing a heavier mass (450 g weight), and maintained the same height as in our previous CHI paradigm. The finding that the 450 g CHI paradigm was associated with a ~20% mortality rate, while our earlier studies indicated no mortality using the milder 250 g CHI paradigm (9,22) points to increased injury severity, and is in agreement with previous studies that investigated the effects of a graded mechanical impact levels (27). Our open-field testing data indicated no change in total distance traveled suggesting no impairment in gross motor activity, similar to the effect of a 250 g weight drop injury.…”
Section: Discussionsupporting
confidence: 90%
“…This dosing regimen has been shown previously to alleviate PTH-like pain behaviors (i.e. cephalic allodynia) following mild CHI in male rats (9,22), and male mice (11), as well as pain behaviors in other chronic migraine models (24).…”
Section: Pharmacological Treatmentsmentioning
confidence: 96%
See 2 more Smart Citations
“…Thus, in PTH it is plausible to hypothesize that direct trauma to the head may be enough to initiate acute periosteal and persistent dural mast cell degranulation for at least 30 days following a trauma, resulting in the development of headache [ 40 , 47 ]. On the other side, Bree and Levy found that persistent activation of meningeal mast cells after mCHI is not required for the development of cephalic hypersensitivity, so that authors hypothesized that CGRP mediates the PTH-related pain behavior through a mechanism independent of ongoing meningeal mast cells pro-inflammatory response [ 68 ].…”
Section: Main Textmentioning
confidence: 99%